Relevant Elements of Standardisation of Federation’s Advisory Programs for Voluntary Sports Clubs - Marisa Moser; Matthias Buser; Siegfried Nagel (Current Issues in Sport Science)
Introduction Sports federations are increasingly inclined to support their member clubs' structural and organisational development (Schlesinger et al., 2021). Thus, federations offer tools and training courses and have started implementing advisory programs supporting voluntary sports clubs' (VSCs') strategic alignment and action (cf. Klenk et al., 2017). However, the effectiveness of external guidance can be limited due to the level of autonomy and independence that VSCs typically show (Nagel & Schlesinger, 2012; Schlesinger et al., 2021). While research has discussed critical interfaces, little is known about what moderates the translation of advisory input to achieve change at club level (cf. Klenk et al., 2017). Hence, this study aimed to gain a deeper understanding of which elements of standardisation in a federation advisory program are relevant for the subsequent implementation in VSCs.